SUMO2 rescues neuronal and glial cells from the toxicity of P301L Tau mutant - Orsini, Franca; Pascente, Rosaria; Martucci, Annacarla; Palacino, Sara; Fraser, Paul; Arancio, Ottavio; Fioriti, Luana (Frontiers in Cellular Neuroscience, 2024)
Introduction Abnormal intracellular accumulation of Tau aggregates is a hallmark of Alzheimer’s disease (AD) and other Tauopathies, such as Frontotemporal dementia (FTD). Tau deposits primarily affect neurons, but evidence indicates that glial cells may also be affected and contribute distinctively to disease progression. Cells can respond to toxic insults by orchestrating global changes in posttranslational modifications of their proteome. Previous studies suggest that SUMOylation, a posttranslational modification consisting of conjugation of SUMO (Small ubiquitin-like modifier) to target proteins, was decreased in the hippocampus of AD patients and in animal model of AD compared with controls. This decrease in SUMOylation was correlated with increased Tau pathology and cognitive decline. Other studies have reported increased levels of SUMO in AD brains. The goal of our study was to evaluate whether SUMO conjugation modifies the neurodegenerative disease pathology associated with the aggregation-prone mutant TauP301L, in neurons and in glial cells. Methods We used viral approaches to express mutant TauP301L and SUMO2 in the hippocampus of wild-type mice. We assessed Tau distribution by immunostaining and Tau aggregation by insolubility assays followed by western blotting. We assessed neuronal toxicity and performed cell count and shape descriptor analyses on astrocytes and microglial cells. Results We found that mutant TauP301L, when expressed exclusively in neurons, is toxic not only to neurons but also to glial cells, and that SUMO2 counteracts TauP301L toxicity in neurons as well as in glia. Discussion Our results uncover an endogenous neuroprotective mechanism, whereby SUMO2 conjugation reduces Tau neuropathology and protects against toxic effects of Tau in glial cells.